2020
DOI: 10.1371/journal.pone.0233700
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β induces interneuron-specific changes in the hippocampus of APPNL-F mice

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by cognitive decline and amyloid-beta (Aβ) depositions generated by the proteolysis of amyloid precursor protein (APP) in the brain. In APP NL-F mice, APP gene was humanized and contains two familial AD mutations, and APP-unlike other mouse models of AD-is driven by the endogenous mouse APP promoter. Similar to people without apparent cognitive dysfunction but with heavy Aβ plaque load, we found no significant decline in the working memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 114 publications
2
12
0
Order By: Relevance
“…Moreover, the present recordings were in the presence of a GABAergic antagonist, which greatly decreased the effects reported in vivo. It should, however, be noted that we do not see alterations in spontaneous GABAergic IPSCs, either here in App knock-in mice, or previously in transgenic mice [10], which is consistent with the observation that palvalbumin-positive interneurones, despite showing some neuritic dystrophy, are otherwise normal in App NL-F mice [48]. Thus, we would not suggest that we could assess the overall physiological network effects of Aβ in the present study but can be confident about the changes seen in individual synapses.…”
Section: Temporal Differences In Loss Of Spontaneous Action Potentials Between Modelssupporting
confidence: 92%
“…Moreover, the present recordings were in the presence of a GABAergic antagonist, which greatly decreased the effects reported in vivo. It should, however, be noted that we do not see alterations in spontaneous GABAergic IPSCs, either here in App knock-in mice, or previously in transgenic mice [10], which is consistent with the observation that palvalbumin-positive interneurones, despite showing some neuritic dystrophy, are otherwise normal in App NL-F mice [48]. Thus, we would not suggest that we could assess the overall physiological network effects of Aβ in the present study but can be confident about the changes seen in individual synapses.…”
Section: Temporal Differences In Loss Of Spontaneous Action Potentials Between Modelssupporting
confidence: 92%
“…Although postmortem human AD brain tissue shows a significant decrease in the abundance of WFA + PNN matrices, one of the earliest PNN characterization studies in the APP/PS1 mouse model of Aβ overexpression showed a significant increase in hippocampal WFA + labeling of parvalbumin neurons as well as a corresponding increase in PNN protein abundance (i.e., neurocan, brevican, link protein, TnR) ( Table 2 ) (Végh et al, 2014 ). In contrast to this finding, two additional mouse lines of Aβ overexpression, Tg2576/APPsw and APP NL−F mice, showed no change in hippocampal PNN abundance or distribution compared to controls (Morawski et al, 2010b ; Sos et al, 2020 ). Further, the abundance of amyloid plaque formation and degree of gliosis in Tg2576/APPsw mice occurred independently of the density and laminar distribution of the PNNs themselves (Morawski et al, 2010b ).…”
Section: Evidence Linking Changes In Perineuronal Nets With Alzheimer...mentioning
confidence: 92%
“…Chondroitin sulfate proteoglycans also protect against soluble β-amyloid: cortical neurons with perineuronal nets resist amyloid protein neurotoxicity in dissociated cultures [ 103 , 113 , 114 ]. This evokes interneuron-specific changes in the brain circuit: parvalbumin-containing interneurons selectively resisted β-amyloid-induced cell damage in an Alzheimer’s disease transgenic mouse model [ 115 ]. The proposed mechanism behind perineuronal nets’ ability to protect neurons is their capacity to bind metal ions which react with free radicals [ 104 ] to trigger and maintain oxidative stress.…”
Section: Extracellular Matrix Components and Neurodegenerative Diseasesmentioning
confidence: 99%